TWO NEW APPLICATIONS OF GENERALIZED (G?/G)- EXPANSION METHOD - Inan, Ibrahim Enam; Ic, Unal (Editura Bibliotheca-Bibliotheca Publ House, 2019)
In this paper, we implemented an Generalized (G/G') - expansion method for some soliton wave solution sixth-order Ramani equation and new Konno-Oono equation system. These solutions are hyperbolic function solutions, trigonometric function solutions, exponential function solutions and rational function solutions. We also saw that the solutions provided the equation using Mathematica 11.2. In addition, graphs of some solutions and numerical explanations of these graphs were given. Recently, this method has been studied for obtaining exact travelling wave solutions of nonlinear partial differential equations.
Keywords: Sixth-order Ramani equation; new Konno-Oono equation system; Generalized (G '/G)- Expansion Method